Pembelajaran Meresensi Buku Ilmu Pengetahuan Melalui Model Skrip Kooperatif di Kelas IX SMPN 1 Gebang - Sri Atin (Peneliti.net, 2020)
This study aims to improve the ability of grade IX students of SMP Negeri 1 Gebang Cirebon Regency in understanding Indonesian language learning materials about “Responding to Science Books with a Cooperative Script model. So that learning Indonesian becomes more memorable and raises creativity. This research data uses quantitative and qualitative approaches together. A qualitative approach is used to provide a description of the views and opinions of research subjects. The quantitative approach is used by recording the events of student learning achievement prior to the existence of the research, then conducting classroom action research in the first and second cycles. Student learning outcomes both individually and in groups have increased in each cycle, the initial results (pre-test) show an average score. -Average 54.77, the results in the first cycle rose to an average score of 67.39, and the results in the second cycle increased to an average score of 80.48